The potential of Acmella oleracea (Jambu) extract in the control of semi-engorged Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) female ticks - de Oliveira, Patrícia Rosa [UNESP]; Anholeto, Luis Adriano [UNESP]; Rodrigues, Rodney Alexandre Ferreira; Bechara, Gervásio Henrique; de Carvalho Castro, Karina Neoob; Camargo Mathias, Maria Izabel [UNESP] (Taylor & Francis, 2018)
The present study evaluated the efficacy of Acmella oleracea extract, and the susceptibility of semi-engorged R. sanguineus females exposed to different concentrations of the extract, with lethal concentration 50 % (LC50) and confidence interval 95%. The ticks were mounted on Petri dishes and immersed in the different concentrations of the extract, distilled water or ethanol 50% + DMSO 1% for 5 minutes, dried and kept in BOD incubator for 7 days. The results showed the daily mortality rate among semi-engorged R.sanguineus females at different concentrations of the extract. The mortality data obtained in bioassay 2 were subjected to Probit analysis, through which a LC50 of 24,883 mg/ml (limits: 22,331 to 28,003 mg/ml) was determined, at a 95% confidence interval. Thus, this study demonstrated the sensitivity and susceptibility of semi-engorged R.sanguineus females to Acmella oleracea extract. The acaricidal potential was effective as from the application of the extract at the concentration of 12.5 mg/ml and was dose-dependent. i.e., higher mortality rates were observed as the concentration increased, with LC50 of 24,883 mg/ml reaching 100% at the concentration of 100 mg/ml in 24h.
Keywords: Extract; natural compound; potential; Rhipicephalus sanguineus; tick